Mimicking Collective Firing Patterns of Hundreds of Connected Neurons using a Single-Neuron Experiment - Goldental, Amir; Sabo, Pinhas; Sardi, Shira; Vardi, Roni; Kanter, Ido (Frontiers in Neuroscience, 2016)
The experimental study of neural networks requires simultaneous measurements of a massive number of neurons, while monitoring properties of the connectivity, synaptic strengths and delays. Current technological barriers make such a mission unachievable. In addition, as a result of the enormous number of required measurements, the estimated network parameters would differ from the original ones. Here we present a versatile experimental technique, which enables the study of recurrent neural networks activity while being capable of dictating the network connectivity and synaptic strengths. This method is based on the observation that the response of neurons depends solely on their recent stimulations, a short-term memory. It allows a long-term scheme of stimulation and recording of a single neuron, to mimic simultaneous activity measurements of neurons in a recurrent network. Utilization of this technique demonstrates the spontaneous emergence of cooperative synchronous oscillations, in particular the coexistence of fast gamma and slow delta oscillations, and opens the horizon for the experimental study of other cooperative phenomena within large-scale neural networks.